Mejorar la comprensión lectora del inglés con estrategias metacognitivas usando herramientas TIC: caso estudiantes de primer semestre de odontología de la Universidad Cooperativa de Colombia (2019)
The learning of a second language in the knowledge society, where most of the information is found everywhere, has become more than a necessity in an imperative, that is to say, a fundamental part of the knowledge to be acquired, taking into account that the information travels through the network in any language and at speeds that were unthinkable a few years ago. The objective of this article is to specify in detail the final results of the research project which shows the possibility that first-semester students of dentistry of the Cooperative University of Colombia improve their process of reading comprehension through the use of metacognitive strategies using learning tools mediated by ICT. The study was based on the possibility of constructing questionnaires where reading comprehension is evident and then giving them some metacognitive learning strategies using ICT tools.